One-pot synthesis of cyclopentadithiophene-isoindigo based low bandgap long-chain π-conjugated oligomers. (March 2020) - Zhang, Xiao-Feng; Liu, Hui; Chen, Yan; Cheng, Jing-Zhao; Wang, Li-Hong; Ye, Dong-Nai; Chen, Long; Liu, Shi-Yong
Graphical abstract: Highlights: Seven low bandgap D-A conjugated oligomers are produced in two separate pots of direct CH arylation reaction. 10.1 nm long oligomer O ′5 involving 6 cyclopentadithiophene and 5 isoindigo units is the longest CPDT or IID based oligomers reported ever. All oligomers and polymer synthesised have low bandgaps between 1.42 ∼1.58 eV. Accurate structure-properties relationships of all oligomers and polymer are studied. Abstract: Two series of cyclopentadithiophene (CPDT) and isoindigo (IID) based donor-acceptor (D-A) low band gap (1.42∼1.58 eV) novel oligomers and their parent polymer have been synthesized via three single pots of direct CH arylation by controlling the feed ratio of IID and CPDT in1.5:1, 1:1.5 and 1:1 respectively. The chain lengths of above two series oligomers with D…D-A-D…D and A…A-D-A…A backbones, respectively, are both increased in a stepwise manner. Among them, the oligomer O 5, involving 6 CPDT units and 5 IID units, is the longest CPDT- or IID-based conjugated oligomers reported ever. The optoelectronic properties of these low band gap oligomers and polymer, which have been studied in detail, are well consistent with their corresponding structural evolution. This work provides an effective synthetic strategy for low band gap monodisperse long-chain D-A oligomers with defined structures that will be of significance for accurate structure-property studies and optic & electronic applications.